Investigação da condutividade hidráulica dos solos de uma área de aterro de resíduos sólidos urbanos por meio de ensaios de campo e laboratório - Jesus, Lucas Scarpanti de [UNESP]; Fernandes, Jeferson Brito [UNESP]; Giacheti, Heraldo Luiz [UNESP] (My University, 2013)
A contaminant plume due to leachate infiltration was found in the solid waste landfill from Bauru, SP. The soil hydraulic conductivity (K) is an important parameter to understand the moving of this plume. This paper intends to show representative K values for the soils that occur in the vicinity of this landfill determined by field and laboratory tests. There are four soil types in the area: colluvium, alluvium, sandstone residual soil and the sandstone. Laboratory tests were performed using constant and variable head in rigid and flexible wall permeameters. Slug tests and hydraulic conductivity tests with the Guelph permeameter were also carried out in situ in the area. Representative K values of 3.7x10-7 m/s for the saturated zone and 2.4x10-8 m/s for the unsaturated zone were determined for the residual soil. A K value of 5.3x10-5 m/s was obtained for the colluvium soil. A great variation of K with depth was observed for the alluvium and the assumed average values for the saturated zone were 7.9x10-7 m/s and 1.1x10-4 m/s for the unsaturated surficial layer. An average K value of 3.3x10-8 m/s was determined in laboratory for the sandstone and it was assumed representative for this material.

Uma pluma de contaminação devido à infiltração de lixiviado foi encontrada no aterro de resíduos sólidos urbanos de Bauru, SP. A condutividade hidráulica (K) do solo é um importante parâmetro para compreender a movimentação dessa pluma. Este artigo visa apresentar valores representativos de K determinados em ensaios de campo e laboratório para os solos que ocorrem nesse aterro. Há quatro tipos de solos na área, coluvião, aluvião, residual de arenito e arenito. Em laboratório foram realizados ensaios em permeâmetros de parede flexível e de parede rígida, a carga constante e variável. No campo realizaram-se ensaios de recuperação em poços de monitoramento e ensaios de condutividade hidráulica com o permeâmetro de Guelph. Como representativos, para o solo residual, encontraram-se valores de K de 3,7x10-7 m/s na zona saturada e de 2,4x10-7 m/s para a zona não saturada. No solo coluvionar obteve-se um valor de K de 5,3x10-5 m/s. Foi encontrada, no aluvião, grande variação de K com a profundidade, assumindo um valor médio de 7,9x10-7 m/s para a zona saturada e de 1,1x10-4 m/s para a camada superficial não saturada. Um valor médio de 3,3x10-8 m/s foi determinado no laboratório para o arenito, o qual foi considerado representativo para esse material.
Investigation of the hydraulic conductivity of soils in an area of municipal solid waste landfill through field and laboratory tests
Keywords: Geo-environmental investigation; Hydraulic conductivity; Solid waste landfill; Tropical soils; Investigação geoambiental; Condutividade hidráulica; Aterro de resíduos sólidos; Solos tropicais